ESTIMASI SEBARAN KARAKTERISTIK ENDAPAN SIRTU BERDASARKAN MODEL DARI VARIOGRAM ELEVASINYA - sedarta, sedarta; Tibri, Tengku Tibri; Onwardana , Eka (LPPM ISTP, 2025)
Due to high demand of natural aggregate for construction aggregates, sand and gravel are one of the most much mined owing to cheap in production cost. Unfortunately, the value is low economically. The exploration is based only on the outcrop or any part of deposit body exposed to surface. The similarity of the topography surface traits is used to estimate the dissemination leading to high risk or uncertainty in the reserve-estimating. Such a deposit however, is a result of sedimentary process which may be re-eroded leaving behind a truncated body or disseminated in the form of lenses. Since the topographic surfaces are result of natural processes, the elevation must depend on one of controlling factors, e.g. geological process. This must comply with a variogram model. Therefore, 3 data sets have been tested; 2 of them related to measurement methods and the other is as a validator. Simulation results disclose that the sand and gravel in Desa Pardamean, Kec. Ajibata – Simalungun is governed by Gaussian or TPL-Stable model variogram with MSER 0.0961-m2. The dissemination is fractal distribution with covered range ±100-m, variation (sill) = 8-m and no nugget. The surface elevation can be estimated using variogram model unless the data set is not representative.